Additive Manufacturing of Micro-Electro-Mechanical Systems (MEMS) - Giorgio De Pasquale (MDPI AG, 2021)
Recently, additive manufacturing (AM) processes applied to the micrometer range are subjected to intense development motivated by the influence of the consolidated methods for the macroscale and by the attraction for digital design and freeform fabrication. The integration of AM with the other steps of conventional micro-electro-mechanical systems (MEMS) fabrication processes is still in progress and, furthermore, the development of dedicated design methods for this field is under development. The large variety of AM processes and materials is leading to an abundance of documentation about process attempts, setup details, and case studies. However, the fast and multi-technological development of AM methods for microstructures will require organized analysis of the specific and comparative advantages, constraints, and limitations of the processes. The goal of this paper is to provide an up-to-date overall view on the AM processes at the microscale and also to organize and disambiguate the related performances, capabilities, and resolutions.